2017
DOI: 10.1002/2211-5463.12201
|View full text |Cite
|
Sign up to set email alerts
|

Thermo‐kinetic analysis space expansion for cyclophilin‐ligand interactions – identification of a new nonpeptide inhibitor using Biacore™ T200

Abstract: We have established a refined methodology for generating surface plasmon resonance sensor surfaces of recombinant his‐tagged human cyclophilin‐A. Our orientation‐specific stabilisation approach captures his‐tagged protein under ‘physiological conditions’ (150 mm NaCl, pH 7.5) and covalently stabilises it on Ni2+‐nitrilotriacetic acid surfaces, very briefly activated for primary amine‐coupling reactions, producing very stable and active surfaces (≥ 95% specific activity) of cyclophilin‐A. Variation in protein c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 73 publications
1
9
0
Order By: Relevance
“…In 20 mM ammonium acetate with pH = 6.8, charge states as low as +7 can be observed, consistent with the work by Barran and co-workers . The plot of CCSs versus charge state (Figure B) and comparison to theoretical CCSs of CypA X-ray structures (PDB IDs 5LUD, 1AWR, and 1AWV ) show that the protein retains its native state at z = +7 and +8. The large increase seen in charge states from z = +8 to z = +9 indicates the unfolding of the native CypA structure as extra charge states accrue, a phenomenon that is well documented for many proteins. …”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…In 20 mM ammonium acetate with pH = 6.8, charge states as low as +7 can be observed, consistent with the work by Barran and co-workers . The plot of CCSs versus charge state (Figure B) and comparison to theoretical CCSs of CypA X-ray structures (PDB IDs 5LUD, 1AWR, and 1AWV ) show that the protein retains its native state at z = +7 and +8. The large increase seen in charge states from z = +8 to z = +9 indicates the unfolding of the native CypA structure as extra charge states accrue, a phenomenon that is well documented for many proteins. …”
Section: Resultssupporting
confidence: 89%
“…(B) CCS of each ion species with its respective charge state for CypA shown in blue. The pink data points correlate to the theoretical CCS of three CypA structures (PDB IDs 5LUD, 1AWR, and 1AWV ). The inset shows the +8 and +9 charge states with their respective CCS of the CycA:CypA complex, and the pink lines show the theoretical CCSs of the X-ray crystal structure (PDB 1CWA ) and NMR structure (PDB 3CYS ) of the complex.…”
Section: Resultsmentioning
confidence: 63%
“…Sensor chip surfaces with active N-terminal His 6 -tagged T. brucei, T. cruzi and L. infantum PFK were generated by using a capture/stabilization method [43,44]. Surface densities corresponding to 1400-3200 resonance units (RU) were immobilized on Ni 2+ -nitrilotriacetic acid sensor chips (GE Healthcare, GE Healthcare Life Sciences, Little Chalfont, Buckinghamshire, UK).…”
Section: Determination Of Kinetic Characteristics Using Pyruvate Kinase-lactate Dehydrogenase Enzymelinked Kinetic Assaymentioning
confidence: 99%
“…Most drug development has focused on the connection between secreted cyclophilins and infectious disease, or the identification of PPIF as a modulator of the mitochondrial permeability transition pore complex [6,7,70]. The majority of this work continues to target the S1 pocket; highly conserved and extremely accessible to solvent, this approach is nearly guaranteed to generate pan-inhibitors with significant off-target activity [8,71,72]. In 2010, we published a study in which we identified and characterized a site contiguous to S1.…”
Section: Spliceophilins: Highly Druggable Modulators Of Nuclear Fumentioning
confidence: 99%